An ethnobotanical survey of traditional medicinal plants used against tuberculosis and symptoms associated in Abidjan, Côte d'Ivoire (Asian Journal of Ethnobiology, 2023)
Abstract. Kande B, Grah ZM, Moyabi AGA, Soro Y, Kone WM. 2023. An ethnobotanical survey of traditional medicinal plants used against tuberculosis and symptoms associated in Abidjan (Côte d'Ivoire). Asian J Ethnobiol 6: 36-45. Infectious diseases, including tuberculosis, are responsible for one-third of the world's mortality due to the mechanism of resistance to antibiotics. Faced with this alarming situation, the search for active principles from natural substances is a primordial need. In this study, semi-structured questionnaires conducted an ethnobotanical survey of medicinal plants used against tuberculosis and associated symptoms in Abidjan. Information was gathered from 171 herbalists. The respondents were asked questions regarding their use of medicinal plants to treat tuberculosis and associated symptoms. Information entailing plants used to treat tuberculosis, associated symptoms, plant parts used, mode of preparation, and dosage was recorded. The results showed that it is known among traditional medicine practitioners to cure tuberculosis but is better understood by its associated symptoms. These surveys revealed a diversity of 41 species of medicinal plants against this disease and its associated symptoms. They are mostly trees. Alchornea cordifolia (Schumach. & Thonn.) Müll.Arg. (Euphorbiaceae), Bombax costatum Pellegr. & Vuillet (Bombacaceae), Ficus sur Forssk. (Moraceae), Kigelia africana (Lam.) Benth. (Bignoniaceae), Nephrolepis bisserata (Sw.) Schott (Nephrolepidaceae), Terminalia glaucescens Planch. ex Benth. (Combretaceae) and Vitellaria paradoxa C.F.Gaertn. (Sapotaceae) are the most cited plant species. Leaves are the most used organs, decoction is the main mode of preparation, and the oral route is the main way to administer the remedies.
Keywords: Côte d'Ivoire, ethnobotanical survey, herbalists, medicinal plants, tuberculosis